"I used to think that they were all abnormal. And I was the normal one": conceptualizing mental health and mental health treatment under Improving Access to Psychological Therapies (IAPT). (2nd September 2016) - Mackinnon, Jessica; Murphy, Helen
Abstract: Background : Improving Access to Psychological Therapies (IAPT) was introduced in the United Kingdom in 2006 to provide more effective and efficient services to people experiencing mild to moderate mental ill health. The model represents a paradigm shift in how we provide psychological care to large populations. Aims : We wanted to document how the IAPT program impacted on patients' understanding of their mental health, and mental health treatment. Methods : We used Foucauldian Discourse Analysis to analyze six semi-structured research interviews with patients from one IAPT service in a major UK city. Results : Participants constructed their mental health problems as individual pathologies. Constructions of mental health and of treatment evidenced the privileging of personal responsibility and social productivity over dependency on others and the state. Conclusions : Services are functioning well for some. The role of IAPT in pathologizing those who are dependent on people and services requires further commentary and action.